BODY COMPOSITION IMPACT ON SURVIVAL AND TOXICITY OF TREATMENT IN PANCREATIC CANCER: CROSS-SECTIONAL PILOT STUDY - BARRÈRE,Ana Paula Noronha (2020)
ABSTRACT BACKGROUND: Weight loss and body composition changes are common in patients with pancreatic cancer. Computed tomography (CT) images are helpful to investigate body composition and its changes and to discriminate the different kinds of body tissues. Patients with pancreatic cancer routinely undergo CT scans. OBJECTIVE: To verify the association of muscle mass and visceral fat measured by CT with toxicity and survival of patients with pancreatic cancer. METHODS: We evaluated the imaging of the abdomen of all consecutive adult patients with pancreatic cancer treated between October 2007 and September 2015 in our service, to assess skeletal muscle mass and fat, intramuscular fat and visceral fat. We graded treatment toxicity symptoms according to the Common Toxicity Criteria of the United States National Cancer Institute (version 2.0). RESULTS: The study involved 17 patients, with a mean age of 63 (±10) years (range: 51-73 years). Eleven (65%) were male. The mean initial body mass index (BMI) was 26 kg/m2 (±3) and 23 kg/m2 (±3) after treatment. The mean weight loss was 10.0 kg (±6.8; 13%). Sarcopenia was present in 47% of patients, and it was not associated with significant differences in muscle mass, visceral fat, toxicity or survival. The mean skeletal muscle attenuation was 36 Hounsfield units, not associated with survival or treatment toxicity. Mean muscle mass was not associated with toxicity either. However, there was a significant inverse association between toxicity and visceral fat. CONCLUSION: Muscle mass had no impact on the survival or on treatment toxicity among the patients with pancreatic cancer. However, the visceral fat exerted a protective effect against the treatment toxicity. We stress the importance of further studies on visceral fat associated with prognosis and toxicity in cancer patients.